Microbiostratigraphy of upper Cretaceous deposits (Bangestan Group) in the northwestern flank of Sepid Kuh anticline, W Iran ... - Maghfouri Moghaddam, Iraj; Khaksar, Keyvan; Darabi, Ghamarnaz; Rahomo Rokrok, Zahra; Besharati, Ziba (Iranian Journal of Earth Sciences, 2023)
The benthic and planktonic foraminiferal contents of the Bangestan Group (Sarvak, Surgah and Ilam formations) in the Sepid Kuh anticline in the Lorestan Zone, W Iran, were studied. Bangestan Group consists of limestone, argillaceous limestone, dolomitic limestone and marl with thickness of 5400 m. In this section Bangestan Group overlies Garu Formation disconformably and its upper boundary is not exposed. By micropaleontological study on 176 thin sections, 8 genus and 34 species planktonic foraminifera were identified. 400 m of Sarvak Formation has very little fossil diversity that does not indicate a certain age. For this reason, this interval was called the indeterminate zone, which due to its stratigraphic position, is probably of Cenomanian age. Based on the biostratigraphical range of planktonic foraminifera distinguished, four biozones can be identified: Helvetoglobotruncana helvetica Total Rang Zone (Early- Middle Turonian), Marginotruncana schneegansi partial Range Zone (late Turonian), Diacarinella ...